Heritability of Bullying and Victimization in Children and Adolescents: Moderation by the KiVa Antibullying Program - Johansson A; Huhtamaki A; Sainio M; Kaljonen A; Boivin M; Salmivalli C (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Objective: Bullying affects approximately a quarter of schoolchildren and is associated with numerous adverse outcomes. Although distinct risk factors for bullying and victimization have been identified, few studies have investigated the genetic and environmental underpinnings of bullying and victimization. The aims of this study were twofold: first, to examine the contributions of genetic and environmental factors to bullying and victimization, and second, to analyze whether the KiVa antibullying program moderated the magnitude of these contributions by comparing estimates derived from the KiVa versus control groups.Method: The sample comprised students from schools that participated in the evaluation of the KiVa antibullying program in Finland during 2007-2009. Bullying and victimization were measured using peer nominations by classmates. The sample for the twin analyses comprised of 447 twins (107 monozygotic and 340 dizygotic twins) aged 7-15.Results: Genetic contributions accounted for 62% and 77% of the variance in bullying and in victimization at pre-intervention, respectively. There was a post-intervention difference in the overall role of genetic and environmental contributions between the intervention and the control group for bullying and victimization, with non-shared environmental effects playing a lesser role (and genes a larger role) in the intervention than in the control group context.Conclusions: This study replicates previous findings on the genetic underpinnings of both bullying and victimization, and indicates that a school-based antibullying program reduces the role of non-shared environmental factors in bullying and victimization. The results indicate that prevention and intervention efforts need to target both environmental and (heritable) individual level factors to maximize effectiveness.